Ratio-dependent competitions between a Wolbachia-uninfected bisexual strain and Wolbachia-infected thelytokous strain of the egg parasitoid, Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae) - Qian-Jin Dong; Yue He; Yu-Zhe Dong; Wu-Nan Che; Jin-Cheng Zhou; Hui Dong (CABI Agriculture and Bioscience)
Abstract Background Wolbachia-infected thelytokous Trichogramma wasps have been considered as potential effective biocontrol agents against lepidopteran pests in agriculture and forests. However, intra-specific competition may arise when Wolbachia-infected thelytokous Trichogramma coexist with their uninfected bisexual counterparts in fields or during mass-rearing procedures. This competition could potentially impact the efficacy of Trichogramma females in biological control programs. Results This study examined the parasitic capacities of bisexual (TdB) and Wolbachia-infected thelytokous (TdT) strains of Trichogramma dendrolimi as influenced by host density (ranging from 5 to 70 host eggs) and wasp density (two, four, and six females per arena). The experiments involved inter-strain competition between TdB and TdT strains (Inter-Td) as well as intra-strain competition within the TdT (Intra-TdT) or TdB (Intra-TdB) strains. Results revealed that females in the Inter-Td group exhibited a higher attack rate compared to those in the Intra-TdT and Intra-TdB groups, irrespective of wasp density. Specifically, when six females were present, the Inter-Td group showed significantly shorter host handling times than the Intra-TdT group. Within intra-strain cohorts, TdT females displayed a lower attack rate than TdB females when four or six females were present, and longer host handling times when six females were present. Mutual interference between individuals was not affected by competition types. Females of the Inter-Td group exhibited a higher probability of superparasitism than those of the Intra-TdB group or Inter-Td group. When both strains coexisted, the proportion of TdT offspring with six females was higher than that with two females or four females. Male ratios of bisexual offspring in Inter-Td groups were higher than those in Intra-TdB groups. The male ratio of bisexual offspring in the Inter-Td group increased with wasp density. Conclusions Our study highlights the negative impact of Wolbachia on parasitic capacity of Trichogramma females, increasing the likelihood of superparasitism. The coexistence of both strains enhances total parasitic efficacy, albeit resulting in a higher proportion of male offspring compared to scenarios with only uninfected females. The results will provide the reference for the usage of Wolbachia-infected thelytokous strain of T. dendrolimi in augmentative biological control programs.